Good Corporate Governance and Profitability on Accounting Conservatism - Lin Oktris; Abd. Rohman Taufiq; Dimas Hasan Samudera; Maisarah Mohamed Saat (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction / Main Objectives: This study examines the effect of good corporate governance mechanisms, consisting of institutional ownership, managerial ownership, and independent commissioners, and profitability on accounting conservatism, with leverage as a moderating variable. Methods: The study uses a quantitative approach with secondary data drawn from financial reports and annual reports of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. A purposive sampling method yielded 31 companies with 93 total observations. Hypotheses were tested using moderated regression analysis with the absolute difference method, processed through SPSS version 26. Results / Findings: The results show that institutional ownership has a significant positive effect on accounting conservatism, while managerial ownership, independent commissioners, and profitability do not produce significant effects. With respect to the moderating role of leverage, the results show that leverage significantly strengthens the positive effect of institutional ownership on accounting conservatism. Leverage does not, however, significantly moderate the effects of managerial ownership, independent commissioners, or profitability on accounting conservatism. Conclusion: These findings indicate that the moderating function of leverage is selective, operating only through governance mechanisms that already demonstrate a direct monitoring effect on accounting conservatism.